Syariah Law and The Rights of Non-Muslims: The Importance of Reinterpreting traditional Syariah And Disseminating Progressive Syariah - Sukron Kamil (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2016)
Abstract During the era of Reformasi the face of Indonesian politics was marked by, among other things, the kindling in a number of regions of the formalizing of Islamic law through regional bylaws, and in other areas through public policy. Efforts to achieve this started at the third level, that is at the level of regulating aspects of religious services and worship, going beyond Islamic family and economic law, and this was also the case with formalizing shariah law at national level.Despite the positive impacts of thissuch as improved security, seen from the perspective of the rights of non-Muslims the implementation of regional Islamic regulations or public policy is a threat, in part because of its positioning as something that may trigger the violation of non-Muslim rights. Examples of this are freedom of worship, freedom to establish schools, the right to take positions of leadership and inter-faith marriage. Moreover, parts of this implementation directly infringe the rights of non-Muslims, such as the obligation to wear a veil. From the Islamic legal perspective, shariah bylaws or regulation have also crossed the boundaries of traditional shariah law, particularly in the requirement to wear a veil and in freedom of worship. Shariah bylaws are a close reflection of traditional Islamic law. Because of this, the shariah law already embodied in regional legislation must be reinterpreted to make it something of benefit to people, providing a sound footing for accomodating such contemporary demands as basic human rights. In any case, the shariah that becomes formalised in bylaws should be progressive and modern, and this is the shariah law that needs to be publicised and supported. Key Words: shariah bylaws,dzimmî, mainstream, hudîûd, khalwat, jizyah, ahl al-kitâb, takwil,and istishlâh. ——- Abstak Selama era reformasi, wajah perpolitikan Indonesia ditandai dengan adanya, antara lain, menjamurnya jumlah daerah-daerah yang memberlakukan hukum Islam melalui peraturan daerah, melalui kebijakan publik.Usaha untuk memeroleh hal ini dilakukan dengan tiga tingkatan, yaitu pada tingkat pemberlakuan aspek-aspek keagamaan, pelayanan dan peribadatan, kemudian berlanjut pada masalah hukum ekonomi dan keluarga islami, dan hal ini juga menjadi masalah pemberlakuan hukum syariah pada tingkat nasional.Meskipun dampak positif semacam ini dapat meningkatkan keamanan, ditinjau dari perspektif hak-hak non-muslim terhadap pemberlakuan peraturan daerah atau kebijakan publik menjadi sebuah ancaman, dikarenakan posisinya sebagai sesuatu yang bisa memicu pelanggaran hak-hak non-muslim. Contohnya adalah kebebasan beribadah, kebebasan medirikan sekolah, hak untuk mengambil alih kepemimpinan dan perkawinan beda keyakinan. Di samping itu, sebagian dari implementasi ini dapat berpengaruh pada pelanggaran hak-hak non-muslim, misalnya kewajiban untuk memakai jilbab. Dari perspektif hukum Islam, hukum/peraturan syariah telah melanggar batas hukum syariah tradisional, khususnya dalam mewajibkan penggunaan jilbab dan kebebasan beribadah.Perda syariah merupakan refleksi hukum islam klasik. Hal ini dikarenakan hukum islam mencakup peraturan daerah yang harus ditafsirkan untuk memberikan manfaat bagi masyarakat, dengan menampung aspirasi suara bawah. Keywords: shariah bylaws,dzimmî, mainstream, hudîûd, khalwat, jizyah, ahl al-kitâb, takwil,and istishlâh.